Condensation of water vapor from humid air inside vertical channels formed by flat plates - Poredoš, Primož; Petelin, Nada; Vidrih, Boris; Žel, Tilen; Ma, Qiuming; Wang, Ruzhu; Kitanovski, Andrej (iScience, 2022)
Condensation of humid air is an important process in thermal and process engineering and a subject of many currently research-intensive scientific domains, such as atmospheric water harvesting and seawater desalination. The nature of (water) vapor condensation in the presence of non-condensable gas (NCG) such as air differs significantly from the case with the pure, quiescent vapor condensation. In the literature, simple models that describe the forced flow condensation of water vapor in the presence of air on a series of vertical flat plates are hard to find. Here we present a simple and computationally efficient semi-empirical correlation describing forced flow condensation from humid air inside vertical channels formed by flat plates. The correlation accounts air as a non-condensing gas, different heights of vertical plates, and different thermal-hydraulic parameters. The correlation has been experimentally validated and shows excellent agreement, as 90% of theoretically predicted values are within ±12% of experimental data. [Display omitted] •Experimental and theoretical study of humid air condensation on vertical plates•Unique condenser geometry was proposed, allowing re-use of condensation latent heat•A new correlation for humid air condensation on a series of plates was proposed•Potential application of correlation for fresh water generation was demonstrated Physics; Interdisciplinary physics; Applied sciences;